3D printing and growth induced bending based on PET-RAFT polymerization. Issue 25 (4th June 2020) - Bainbridge, Chris William Anderson; Engel, Kyle Edward; Jin, Jianyong
Abstract : We demonstrated a method for PET-RAFT growth induced bending of a 3D printed strip using visible light, where the growth on one side of the strip causes stress and the strip bends accordingly to reach a more comfortable position. Abstract : 4D printing has steadily become an emerging area of advanced manufacturing research and has produced some truly fantastic innovations. Previously we have demonstrated the 3D printing process based on PET-RAFT polymerization, and its subsequent capability in the post-production modification of surface properties. In this work, (1) we further optimized the PET-RAFT 3D printing formulation by replacing RAFT agent CDTPA with BTPA and adjusting the monomer composition; (2) we also observed the photodegradation of the photocatalysts EB and EY under 405 nm light and the effects this has on 3D printing; (3) we then did successful 3D printing using a commercial 405 nm DLP 3D printer, with an improved build speed of up to 2.29 mm h −1 ; (4) lastly, for the first time we have demonstrated a method for growth induced bending of a 3D printed strip, where the growth on one side of the strip causes stress and the strip bends accordingly to reach a more comfortable position.